"Prevention of opioid use disorder: the HOME (housing, opportunities, motivation and engagement) feasibility study" - Kelly J. Kelleher; Ruri Famelia; Tansel Yilmazer; Allen Mallory; Jodi Ford; Laura J. Chavez; Natasha Slesnick (BMC, 2021)
Abstract Young adults experiencing homelessness are at high risk of opioid and other substance use, poor mental health outcomes, exposure to trauma, and other risks. Providing access to stable housing has the potential to act as a powerful preventive intervention, but supportive housing programs have been studied most often among chronically homeless adults or adults with serious mental illness. The Housing First model, which does not precondition supportive housing on sobriety, may reduce drug use in homeless adults. In the present study, we piloted an adapted model of Housing First plus prevention services that was tailored to the needs of young adults (18-24 years) experiencing homelessness in the USA. Preventive services were added to the Housing First model and included youth-centered advocacy services, motivational interviewing, and HIV risk prevention services. This model was piloted in a single-arm study (n = 21) to assess the feasibility, acceptability, and initial efficacy of a Housing First model over a 6-month period in preparation for a larger randomized trial. We use repeated measures ANOVA to test for changes in alcohol and drug use (percent days of use; alcohol or drug use consequences), housing stability, social network support, and cognitive distortions over 6 months of follow-up. A total of 17 youth completed the study (85% retention), and a high proportion of youth were stably housed at 6-month follow-up. Participation in intervention services was high with an average of 13.57 sessions for advocacy, 1.33 for MI, and 0.76 for HIV prevention. Alcohol use did not change significantly over time. However, drug use, drug use consequences, and cognitive distortions, and the size of youths' social networks that were drug using individuals decreased significantly. The Housing First model appeared to be feasible to deliver, and youth engaged in the supportive intervention services. The study demonstrates the potential for an adapted Housing First model to be delivered to youth experiencing homelessness and may improve outcomes, opening the way for larger randomized trials of the intervention.